Dodging the Host Interferon-Stimulated Gene Mediated Innate Immunity by HIV-1: A Brief Update on Intrinsic Mechanisms and Counter-Mechanisms - Chintala, Kumaraswami; Mohareer, Krishnaveni; Banerjee, Sharmistha (Frontiers in Immunology, 2021)
Host restriction factors affect different phases of a viral life cycle, contributing to innate immunity as the first line of defense against viruses, including HIV-1. These restriction factors are constitutively expressed but triggered upon infection by interferons. Both pre-integration and post-integration events of the HIV-1 life cycle appear to play distinct roles in the induction of interferon-stimulated genes (ISGs), many of which encode antiviral restriction factors. However, HIV-1 counteracts the mechanisms mediated by these restriction factors through its encoded components. Here, we review the recent findings of pathways that lead to the induction of ISGs and the mechanisms employed by the restriction factors such as IFITM, APOBEC, MX2, and ISG15 in preventing HIV-1 replication. We also reflect on the current understanding of the counter-mechanisms employed by HIV-1 to evade innate immune responses and overcome host restriction factors. Overall, this mini-review provides recent insights into the HIV-1-host cross-talk bridging the understanding between intracellular immunity and research avenues in the field of therapeutic interventions against HIV-1.